2013
DOI: 10.3389/fmicb.2013.00332
|View full text |Cite
|
Sign up to set email alerts
|

Purification, biochemical characterization and self-assembled structure of a fengycin-like antifungal peptide from Bacillus thuringiensis strain SM1

Abstract: An antifungal lipopeptide fengycin, producing strain SM1 was isolated from farm land soil sample and identified as Bacillus thuringiensis strain SM1 by using 16S rDNA analysis. Fengycin detected in the culture extract was further purified using HPLC and showed a molecular mass of 1492.8 Da by MALDI-TOF-MS analysis. Purified fengycin was allowed to construct their self-assembled structure onto a hydrophobic surface showing a clear improvement of antibacterial activity. In self-assembly, fengycin adapts a spheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…Fengycin is known to affect the biological membranes of fungi, causing membrane pore formation, however, the precise mechanism of fengycin's action and the intrinsic biochemical determinants implicated in its antifungal activity have not been fully elucidated [31]. Simultaneous production of fengycins and surfactins could be important for the efficiency of F. graminearum control by strain B. subtilis SG6 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Fengycin is known to affect the biological membranes of fungi, causing membrane pore formation, however, the precise mechanism of fengycin's action and the intrinsic biochemical determinants implicated in its antifungal activity have not been fully elucidated [31]. Simultaneous production of fengycins and surfactins could be important for the efficiency of F. graminearum control by strain B. subtilis SG6 [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the integral values of NOE i À i + 3 and NH-NH are in the same order of magnitude, suggesting close spatial distances (Table S3). On the other hand, the interactions i À i + 3 and NH-NH for 5HN-2HA and 9HN-8HN, show clear differences due to structural flexibility caused by 4 Gly and 8 Gly, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, in addition to multiple functions, there are also a wide number of AMP sources including microorganisms, invertebrates, animals and plants [3][4][5]. In the case of plant tissues, AMPs have also been isolated from flowers, leaves, roots and seeds, among others [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…B. megaterium, B. coagulans, B. thuringiensis BT2 and several B. amyloliquefaciens isolates demonstrated both strong biosurfactant activity and suppression of B. cinerea, F. pallidoroseum, and F. moniliforme, implying the ability to synthesize antifungal lipopeptides. The production of antifungal lipopeptides has been identified in other strains of the species of Bacillus used in this study, including B. amyloliquefaciens [11,12,24], B. coagulans [21], B. megaterium [23], and B. thuringiensis [15,16,57]. B. pumilus and O. sojae demonstrated weak biosurfactant activity but no fungal suppression.…”
Section: Bacillus Species Oceanobacillus Sojae and Ochrobactrum Antmentioning
confidence: 90%